New perspectives on the Bronze Age : proceedings of the 13th Nordic Bronze Age Symposium held in Gothenburg 9th to 13th June 2015 /: proceedings of the 13th Nordic Bronze Age Symposium held in Gothenburg 9th to 13th June 2015. ([2017]) - Unknown
No abstract available